Efficacy of Co-Parenting for Successful Kids: A Longitudinal Pilot Investigation. Issue 8 (17th November 2019) - Choi, Jeong-Kyun; Wang, Dan; Reddish, Linda; Brand, Gail
ABSTRACT: With a sample of 155 divorcing parents, this study examined the efficacy of a co-parenting program titled Co-Parenting for Successful Kids (CPSK). A prospective longitudinal cohort study was used to assess parental outcomes at multiple time points (i.e., pre-test, post-test, and three-month follow-up). Using validated scales, we measured parenting stress, parenting self-efficacy, and parental anger over time. The results indicated that the participants experienced reduced parenting stress and parental anger, and increased parenting self-efficacy after completion of the co-parenting program. Co-parenting interventions to help divorcing parents with stress management, and continuously work together collaboratively in raising their children should be encouraged.